Gatekeeping at two main Belgian comics publishers, Dupuis and Lombard, at a time of transition (in the 1980s). Issue 1 (1st July 2015) - Lefèvre, Pascal
Comics studies have not paid much attention to the functioning of comics publishers, although they remain a crucial factor in the selection, creation, distribution and promotion of comics. An important methodological framework, the gatekeeping research, may offer possibilities as is demonstrated in this historical study of two important comics publishers, Dupuis and Lombard (conducted in the summer 1985). On the basis of an exploratory gatekeeping study at the editorial offices of the two publishers and various contemporary interviews with both gatekeepers (editorial staff) and artists, the gatekeeping process is traced out: how were comics selected, how was the interaction between editors and creators, who were the gatekeepers, and what were their criteria for selecting comics suited for publication (in a weekly or as an album). The results of this research were published in 1986 as a master's thesis in Dutch (in English the translated title is 'The selecting comics publishers: A gatekeeping study of two big Belgian comics publishers Lombard and Dupuis'), but were never published in any other language afterwards.